2013
DOI: 10.1128/jvi.00611-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Human Herpesvirus 6A gQ1 Domain Essential for Its Functional Conformation

Abstract: cHuman herpesvirus 6 is a T lymphotropic herpesvirus, long classified into variants A and B (HHV-6A and HHV-6B) based on differences in sequence and pathogenicity. Recently, however, HHV-6A and HHV-6B were reclassified as different species. Here, we isolated a neutralizing monoclonal antibody (Mab) named AgQ 1-1 that was specific for HHV-6A glycoprotein Q1 (AgQ1), and we showed that amino acid residues 494 to 497 of AgQ1 were critical for its recognition by this Mab. This region was also essential for AgQ1's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…Previously, we reported that amino acid residues 494 to 497 of HHV-6A gQ1 and 484 to 496 of HHV-6B gQ1 are important for the function of gQ1 proteins (11,19). Here, we found that an E127Q mutation in HHV-6B gQ1 could completely abolish its function.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Previously, we reported that amino acid residues 494 to 497 of HHV-6A gQ1 and 484 to 496 of HHV-6B gQ1 are important for the function of gQ1 proteins (11,19). Here, we found that an E127Q mutation in HHV-6B gQ1 could completely abolish its function.…”
Section: Discussionsupporting
confidence: 51%
“…6B). As mentioned previously, the HHV-6B gH/gL/ gQ1/gQ2 complex did not bind to CD46 (12), even when HHV-6B gQ1 formed a complex with HHV-6A gH, gL, and gQ2 (19) (Fig. 6C).…”
Section: Fig 3 Soluble Cd134 Blocks Hhv-6b Infection Soluble Cd134 Pmentioning
confidence: 71%
See 1 more Smart Citation
“…Receptors are targets for neutralization [24] and can be used to create receptor-transgenic animal models that support infection [25]. The essential components for membrane fusion by HHV-6A and HHV-6B are gB and the gH/gL/gQ1/gQ2 complex [26-28]. gQ2 and gM are essential for virus production of HHV-6A since virus stocks could not be generated from BACs with disruptions in these ORFs [28,29].…”
Section: Productive Replicationmentioning
confidence: 99%
“…MAb 87-y-13 does not neutralize rHHV-6A BACgB(N347K) or rHHV-6A BACgB(N347A) infection. We reported previously that the MAb against HHV-6A gQ1 (AgQ1-1) has high neutralizing activity for HHV-6A but not for HHV-6B (25) and that the MAb against HHV-6B gQ1 (KH-1) has high neutralizing activity for HHV-6B but not for HHV-6A (26). Here we tested whether MAb 87-y-13 would block infection by rHHV-6A BACgB(N347K) or rHHV-6A BACgB(N347A), and we compared the action of MAb 87-y-13 with the neutralizing activities of Mabs AgQ1-1 and KH-1.…”
Section: Resultsmentioning
confidence: 99%